Minimise Environmental Pollution Due To the Use of Vegetable Oil as an Alternative Fuel in Diesel Engine - Alaa Musalam (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Gaza Strip has a long history of critical shortage in its fuel supply due to the economic siege imposed by the Israeli national policy. Not surprisingly, therefore, alternative solutions have been sought ever since which replace the use of diesel in car engines with all kinds of vegetable oils. Nevertheless, such alternative shows drawbacks in relation to badly affecting the surrounding environment. This study focuses on these drawbacks in an effort to minimise environmental pollution emerged due to using vegetable oil as an alternative energy resource to fuel engine. In so doing, analysis in this article uses the Gaza Strip as a particular case. A comparison is utilised in this case through the lens of heat efficiency which compares between the proportions of environmental pollution, firstly emerged due to the combustion of vegetable oil and secondly occurred in the engine diesel. The next step seeks to minimize the proportion adopting handling heating that uses additional materials, small organic molecules, acetone and toluene. These materials reduce environmental pollution in comparison with diesel engine, thereby enhancing its efficiency. Analysis in this study uses three different mixtures of alternative fuels based on vegetable oil (VO). In the first fuel, the VO contains different percentage of acetone. The second one has VO with different percentage of diesel. The last fuel shows 80%VO, 20% diesel and different percentage of acetone. This study argues that the best performance similarly to the efficiency of fuel diesel was measured at 2%-10% acetone for the first mixture, 20%-40% diesel for the second one and at 5%-10% acetone for the last one. From the perspective of ecology, the third mixture reveals the best outcomes amongst others because it minimises the CO2 emissions in relation to the VO. It reaches between 13.5% and 15%. In a similar vein, the NO2 emission was minimized at a percentage that reaches between 4% and 16%. All the above results were accepted at α=1 due to balancing between CO2 and NO2 emissions.